An Approximate Analysis of Insulation Thickness of Elliptic Pipe. Issue 1 (August 2020) - Shi, Jinsheng; Zhang, Qiaozhen
Abstract: The thermal insulation characteristics of elliptic pipe were analyzed preliminarily. Thermal resistances between elliptic pipe line to surrounding ambient were studied in dimensionless form. The expression for critical insulation thickness was obtained. The lower bound thickness and heat transfer rate were researched. Influences of different factors were discussed. It is found that for cases of small Biot number, the lower bound thickness is obviously greater than the critical thickness. And the addition of insulation material upon elliptic pipe line should be conducted enough so that the insulation layer exceeds the lower bound thickness in order the insulation investment play a positive role.